Policies and Procedures for Granting Advanced Standing - Chickering, Arthur W.; State Univ. of New York, Saratoga Springs. Empire State Coll. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
The policies and procedures for granting advanced standing at Empire State College are based on three requirements. First, the learnings for which recognition is requested must be articulated. Second, the learnings must be pertinent to the student's goals and consistent with the educational goals of the college. Third, evidence must be generated in support of the learnings claimed. Two basic steps by which advanced standing is granted include portfolio preparation and application by the student and evaluation by the college. The portfolio is organized in three sections: an initial summary, a general essay, and an appendix of supporting evidence. Time requirements and records, including the transcript statement and portfolio, are reviewed. (MJM)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Advanced Placement; Advanced Placement Programs; Advanced Students; College Students; Higher Education; School Policy; State University of New York Empire State Coll